Agricultural nutrient loadings to the freshwater environment: The role of climate change and socioeconomic change - Xie, Hua; Ringler, Claudia (IOP Publishing, 2017)
Human activities, in particular agricultural production, interfere with natural cycles of nutrient elements, nitrogen (N) and phosphorus (P), leading to growing concerns about water quality degradation related to excessive nutrient loadings. Increases in agricultural production in response to population growth and wealth generation further increase risks associated with nutrient pollution. This paper presents results from projections of nutrient exports from global agricultural crop and pasture systems to the water environment generated using a process-based modeling approach. Brazil, China, India and the United States account for more than half of estimated global N and P loadings in the base year. Each country boasts large agriculture centers where high calculated loading values are found. Rapid growth in global agricultural nutrient loadings is projected. Growth of agricultural pollution loading is fastest in the group of low-income developing countries and loading growth rates also vary substantially with climate change scenario. Counter measures need to be taken to address the environmental risks associated with the projected rapid increase of agricultural nutrient loadings.